Redistribution of lower-extremity joint moments during alpine skiing - Simons, C.; Decker, M.; Seifert, J.; Shelburne, K.; Sterett, W.; Davidson, B. (Science and Skiing VII, 2018)
The sagittal plane knee joint moment is a surrogate measure of knee loading. Changes in the magnitude of this moment with a specific intervention are often attributed to alterations in the magnitude of the ground reaction force (GRF) or the length of the lever arm between the GRF and knee joint center. The product of these two variables comprise the simplified lever-arm method of computing joint moments (Hof, 2000). A directional pattern of multiple fabric elasticities built into a pair of compression tights has been found to reduce self-reported values of knee pain and quadriceps fatigue on average by 26% and 29% in professional skiers (Decker, 2013). Coordinated hip-, knee-, and ankle-joint motions during a ski turn influences the location and orientation of the ground reaction force consequently altering the distribution of lower-extremity joint moments and the mechanical stress across the knee joint. The purpose of this study was to apply the lever-arm method of measuring joint moments to determine the effects of a wearable, knee-loading intervention device during alpine skiing.